CSR as a Social Investment Chain: Building Digital Capabilities and Employability through School-Based Institutional Practice - Hannin Pradita Nur Soulthoni; Dewi Yosepin Wijayanti (UIN Sunan Kalijaga Yogyakarta, 2025)
This study examines how Corporate Social Responsibility (CSR) functions as a social investment chain to develop digital capabilities and enhance employability through institutional practices within secondary schools. Building on the evolving perspective of CSR-from a moral obligation to a strategy for creating shared value-this research employs a qualitative case study approach at SMK Forward Nusantara Depok, Indonesia. Data were collected through in-depth interviews, observations, and document analysis involving company representatives, school leaders, teachers, and students. The findings reveal that CSR extends beyond merely providing resources; it operates as a multi-tiered process encompassing investment in digital access, institutional capacity building, and the cultivation of student employability. Digital facilities are transformed into sustainable learning practices through teacher training, curriculum integration, and school governance, enabling students to produce digital projects, build portfolios, and foster independent learning. These practices exemplify social investment mechanisms at the micro level that cultivate future-oriented capabilities. This study contributes to the CSR and welfare literature by conceptualizing CSR as a social investment chain grounded in institutional practices and offers practical implications for designing CSR programs focused on educational capacity building. Keywords: Corporate Social Responsibility, Vocational Education Quality, Industry-Education Collaboration Penelitian ini mengkaji bagaimana Corporate Social Responsibility (CSR) berfungsi sebagai rantai investasi sosial dalam pengembangan kapabilitas digital dan peningkatan daya kerja (employability) melalui praktik-praktik institusional di tingkat sekolah menengah kejuruan. Berangkat dari perkembangan perspektif CSR, dari kewajiban moral menuju strategi penciptaan nilai bersama (creating shared value), penelitian ini menggunakan pendekatan studi kasus kualitatif yang berlokasi di SMK Forward Nusantara Depok, Indonesia. Pengumpulan data dilakukan melalui wawancara mendalam, observasi, serta analisis dokumen yang melibatkan perwakilan perusahaan, pimpinan sekolah, guru, dan peserta didik. Temuan penelitian menunjukkan bahwa CSR tidak hanya berperan sebagai mekanisme penyediaan sumber daya, tetapi juga beroperasi sebagai proses berlapis yang mencakup investasi pada akses digital, penguatan kapasitas institusional sekolah, serta pembentukan daya kerja peserta didik. Fasilitas digital yang disediakan melalui program CSR ditransformasikan menjadi praktik pembelajaran berkelanjutan melalui pelatihan guru, integrasi kurikulum, dan penguatan tata kelola sekolah. Proses ini memungkinkan peserta didik untuk menghasilkan proyek digital, membangun portofolio keterampilan, serta mengembangkan pembelajaran mandiri yang berorientasi pada masa depan. Praktik-praktik tersebut mencerminkan mekanisme investasi sosial pada level mikro yang berkontribusi pada penguatan kapabilitas generasi muda. Studi ini memberikan kontribusi pada literatur CSR dan kesejahteraan dengan mengonseptualisasikan CSR sebagai rantai investasi sosial yang berakar pada praktik institusional, sekaligus menawarkan implikasi praktis bagi perancangan program CSR yang berfokus pada penguatan kapasitas pendidikan. Kata kunci: Corporate Social Responsibility; kualitas pendidikan kejuruan; kolaborasi industry-pendidikan